Congenital pneumonia with empyema at birth; a rare presentation - Sabal, Saransh; Tiwari, Kavita; Poswal, Lakhan (International Journal of Contemporary Pediatrics, 2017)
Empyema thoracis is a rare complication of congenital pneumonia in neonates. Case characteristics: A newborn presented with severe respiratory distress had empyema thoracis. Outcome: patient was managed with chest tube insertion and antibiotics. Message: empyema can be a rare complication of congenital pneumonia and along with appropriate antibiotics, chest tube drainage is required for successful management.